2018
DOI: 10.1523/jneurosci.0896-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Hyperpolarization-Activated Cyclic Nucleotide-Gated Channel Function in Thalamocortical Neurons Prevents Genetically Determined and Pharmacologically Induced Absence Seizures

Abstract: Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels and the Ih current they generate contribute to the pathophysiological mechanisms of absence seizures (ASs), but their precise role in neocortical and thalamic neuronal populations, the main components of the network underlying AS generation, remains controversial. In diverse genetic AS models, Ih amplitude is smaller in neocortical neurons and either larger or unchanged in thalamocortical (TC) neurons compared with nonepileptic strains. A lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 70 publications
2
26
2
Order By: Relevance
“…be part of the pathomechanism leading to seizures (29,42). Previous rodent models for absence epilepsy have focused on abnormal cortical activity and on a perturbation of cortically controlled feedforward inhibition of TC cells through the nRT (43,44). Absence epilepsy was also found in animals deficient in corticoreticular excitation, which leads to a hyperexcitability of TC cells due to the lack of feedforward inhibition (45).…”
Section: Discussionmentioning
confidence: 99%
“…be part of the pathomechanism leading to seizures (29,42). Previous rodent models for absence epilepsy have focused on abnormal cortical activity and on a perturbation of cortically controlled feedforward inhibition of TC cells through the nRT (43,44). Absence epilepsy was also found in animals deficient in corticoreticular excitation, which leads to a hyperexcitability of TC cells due to the lack of feedforward inhibition (45).…”
Section: Discussionmentioning
confidence: 99%
“…Channelopathies in several ion channels have been identified as possible pathophysiological mechanisms of absence seizures in both humans and animal models . Among these different voltage‐gated ion channels, hyperpolarization‐activated cyclic nucleotide‐gated (HCN) channels and the mediated I h currents are proposed to contribute to network excitability and seizure expression in genetic models of absence epilepsy . Moreover, a reduction in HCN2 mRNA levels was also observed in fully kindled animals in the CA3 region .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported alterations in the expression of HCN, in particular, HCN1 and HCN2, in different types of epilepsy in both mice and humans (for review (41,54)). One recent study reported that blocking HCN1 channel activity prevented absence seizures (55), suggesting that an increase in HCN1 channel expression contributes to the generation of absence seizures. Another study reported no change in HCN4 expression in the hippocampus following febrile seizures despite changes in HCN1 (56).…”
Section: Discussionmentioning
confidence: 99%